BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Esperanto for histones: CENP-A, not CenH3, is the centromeric histone H3 variant - W. C. Earnshaw; R. C. Allshire; B. E. Black; K. Bloom; B. R. Brinkley; W. Brown; I. M. Cheeseman; K. H. A. Choo; G. P. Copenhaver; J. G. DeLuca; A. Desai; S. Diekmann; et al. (Chromosome Research, 2013)

Water use efficiency among dry bean landraces and cultivars in drought-stressed and non-stressed environments - Carlos German Muñoz-Perea; Richard G. Allen; Dale T. Westermann; James L. Wright; Shree P. Singh (Euphytica, 2007)

Nutritional requirements of potatoes - D. T. Westermann (American Journal of Potato Research, 2005)

Hereditary hemorrhagic telangiectasia: ENG and ALK-1 mutations in Dutch patients - T. G. W. Letteboer; R. A. Zewald; E. J. Kamping; G. de Haas; J. J. Mager; R. J. Snijder; D. Lindhout; F. A. M. Hennekam; C. J. J. Westermann; J. K. Ploos van Amstel (Human Genetics, 2005)

Some unique benefits with sudangrass for improved U.S. #1 yields and size of Russet Burbank potato - J. R. Davis; O. C. Huisman; D. T. Westermann; D. O. Everson; A. Schneider; L. H. Sorensen (American Journal of Potato Research, 2004)

A genetic linkage map of rye (Secale cereale L.) - V. Korzun; S. Malyshev; N. Kartel; T. Westermann; W. E. Weber; A. Börner (Theoretical and Applied Genetics, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Nutrient concentration relationships between the fourth petiole and upper-stem of potato plants - D. T. Westermann; S. M. Bosma; M. A. Kay (American Journal of Potato Research, 1994)

Nitrogen and potassium fertilization of potatoes: Sugars and starch - D. T. Westermann; D. W. James; T. A. Tindall; R. L. Hurst (American Journal of Potato Research, 1994)

Nitrogen and potassium fertilization of potatoes: Yield and specific gravity - D. T. Westermann; T. A. Tindall; D. W. James; R. L. Hurst (American Journal of Potato Research, 1994)

Nitrogen and potassium fertilization of potatoes: Evaluating nutrient element interactions in petioles with response surfaces - D. W. James; R. L. Hurst; D. T. Westermann; T. A. Tindall (American Journal of Potato Research, 1994)

Comparison of Russet Burbank yield and quality under furrow and sprinkler irrigation - T. J. Trout; D. C. Kincaid; D. T. Westermann (American Journal of Potato Research, 1994)

Potato response to split nitrogen timing with varying amounts of excessive irrigation - J. C. Stark; I. R. McCann; D. T. Westermann; B. Izadi; T. A. Tindall (American Journal of Potato Research, 1993)

Irrigation and soil temperature effects on Russet Burbank quality - D. C. Kincaid; D. T. Westermann; T. J. Trout (American Journal of Potato Research, 1993)

Zone-subsoiling effects on potato yield and grade - R. E. Sojka; D. T. Westermann; D. C. Kincaid; I. R. McCann; J. L. Halderson; M. Thornton (American Journal of Potato Research, 1993)

Errata - D. T. Westermann; J. R. Davis (American Journal of Potato Research, 1993)

Potato nutritional management changes and challenges into the next century - D. T. Westermann; J. R. Davis (American Journal of Potato Research, 1992)

Fertility and management practices to control verticillium wilt of the russet burbank potato - J. R. Davis; L. H. Sorensen; J. C. Stark; D. T. Westermann (American Journal of Potato Research, 1990)

Nitrogen fertilizer efficiencies on potatoes - Dale T. Westermann; Gale E. Kleinkopf; Lynn K. Porter (American Journal of Potato Research, 1988)

Specific gravity of Russet Burbank potatoes - G. E. Kleinkopf; D. T. Westermann; M. J. Wille; G. D. Kleinschmidt (American Journal of Potato Research, 1987)